Sarajevo as seen by Miljenko Jergović - Michalska, Julia (Mundus Slavicus I, 2025)
In the article Sarajevo as seen by Miljenko Jergović I try to analyse Jergović’s short stories from the perspective of geopoetics. I aim to depict Sarajevo that Jergović looked at during the siege, which was also the last period he lived there, and to determine what kind of influence the city had on its inhabitants and on shaping of their identities. I characterise several places mentioned in writings, and I try to analyse how they influenced the characters, what they associate with these places and what these places meant to them.